Otis & Peanut - Hrab, Naseem; Collier, Kelly (2023)
"A long-haired guinea pig and a naked mole rat may seem like unlikely friends, but Otis and Peanut perfectly support one another's quirks and foibles. A graphic novel in the spirit of Frog and Toad, these three delightful stories explore themes like friendship, grief, fear of change, and belonging, and they do it in a light and humorous way that will warm the hearts of every reader. In "The Haircut," Otis worries about getting a haircut because he's afraid he'll look so different he'll no longer be himself. In "The Swing," Peanut helps Otis come to terms with missing a beloved friend. And in "The House," Otis struggles to make his house a home with Peanut's help. These two endearing characters gently explore deep truths about life and human nature, while helping each other figure out their world."--Provided by publisher.
The haircut -- The swing -- The house.
Series numbering from spine.
Ages 8-12
Keywords: Friendship -- Comic books, strips, etc; Guinea pigs -- Comic books, strips, etc; Moles (Animals) -- Comic books, strips, etc; Graphic novels -- Canada; Friendship -- Juvenile fiction; Guinea pigs -- Juvenile fiction; Friendship -- Fiction; Guinea pigs -- Fiction; Cartoons and comics; Graphic novels; JUVENILE FICTION / Social Themes / Friendship; JUVENILE FICTION / Social Themes / Emotions & Feelings; JUVENILE FICTION / Social Themes / New Experience; JUVENILE FICTION / Comics & Graphic Novels / Animals; Graphic novels; Comics (Graphic works); Graphic novels; Graphic novels; Comics (Graphic works); Animal comics; Humorous comics